Epitypification of Gastrodia pubilabiata (Gastrodieae, Epidendroideae, Orchidaceae) - Suetsugu, Kenji; Fukunaga, Hirokazu; Sawa, Shinichiro (Phytotaxa, 2018)
The genus Gastrodia Brown (1810: 330; Gastrodieae, Epidendroideae) is distributed throughout the temperate and tropical regions of Asia, Oceania, Madagascar, and Africa (Cribb et al. 2010; Govaerts et al. 2016). The genus is characterized by its fleshy tubers, lack of leaves, united sepals and petals, and the production of two mealy pollinia that lack caudicles. Several recent studies have re-examined the diversity of Gastrodia species in various Asian countries (Ong & O’Byrne 2012; Suetsugu 2013, 2014, 2016, 2017; Hu et al. 2014; Huang et al. 2015; Ong 2015; Hsu et al. 2016; Pelser et al. 2016; Tsukaya & Hidayat 2016), and as a result, the genus has been updated to include more than 90 accepted species, thereby making it the most species-rich genus among mycoheterotrophic plants.